1990
DOI: 10.1139/y90-155
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the risk assessment of three mycotoxins: aflatoxin, ochratoxin, and zearalenone

Abstract: The risk assessment of mycotoxins is made up of two major components: an exposure assessment and a hazard assessment. There are many uncertainties in both of these components. This paper will briefly discuss the various aspects of the risk assessment process as it applies to mycotoxins and will then focus mainly on some of the uncertainties in the hazard assessment component of several carcinogenic mycotoxins. To arrive at an estimated "safe dose" (end point of the hazard assessment), we have previously used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
8

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(77 citation statements)
references
References 12 publications
0
69
0
8
Order By: Relevance
“…day À1 for AFM 1 based on a risk level of 10 À5 . The value of estimated AFM 1 intake through milk by this exposure assessment is 25 times lower than the TDI proposed by Kuiper-Goodman (1990). This preliminary data showed that estimated exposure to AFM 1 through milk consumption does not represent a serious toxicological risk for Turkish adults.…”
Section: Estimated Daily Intake Of Afmmentioning
confidence: 58%
“…day À1 for AFM 1 based on a risk level of 10 À5 . The value of estimated AFM 1 intake through milk by this exposure assessment is 25 times lower than the TDI proposed by Kuiper-Goodman (1990). This preliminary data showed that estimated exposure to AFM 1 through milk consumption does not represent a serious toxicological risk for Turkish adults.…”
Section: Estimated Daily Intake Of Afmmentioning
confidence: 58%
“…Thus, there are not TDI for AFM 1 . Alternatively, estimates of safe intake can be determined dividing the TD 50 (the daily dose rate in mg/kg bw per day to induce tumours in half test animals that would have remained tumor-free at zero dose) by an uncertainty factor of 5000, a value equivalent to a risk level of 1:100,000 (Kuiper-Goodman, 1990). This approach can, therefore, be used for both genotoxic and non-genotoxic agents, which is especially useful when there is some uncertainty regarding the mode of action (Kuiper-Goodman, 1996).…”
Section: Tablementioning
confidence: 99%
“…Several reviews on different aspects of OTA have been published including overviews on general aspects [12,13,14,15,16], on OTA as a storage mycotoxin [17], on OTA and its mode of action [18,19,20], on carcinogenic potential of OTA [21], on general risk assessment of OTA [22] or on decontamination [23,24]. …”
Section: Introductionmentioning
confidence: 99%